Does Ultrasound‐Enhanced Instruction of Musculoskeletal Anatomy Improve Physical Examination Skills of First‐Year Medical Students?. (10th August 2017) - Walrod, Bryant J.; Schroeder, Allison; Conroy, Mark J.; Boucher, Laura C.; Bockbrader, Marcia; Way, David P.; McCamey, Kendra L.; Hartz, Clinton A.; Jonesco, Michael A.; Bahner, David P.
Abstract : Objectives: Ultrasound imaging is commonly used to teach basic anatomy to medical students. The purpose of this study was to determine whether learning musculoskeletal anatomy with ultrasound improved performance on medical students' musculoskeletal physical examination skills. Methods: Twenty‐seven first‐year medical students were randomly assigned to 1 of 2 instructional groups: either shoulder or knee. Both groups received a lecture followed by hands‐on ultrasound scanning on live human models of the assigned joint. After instruction, students were assessed on their ability to accurately palpate 4 anatomic landmarks: the acromioclavicular joint, the proximal long‐head biceps tendon, and the medial and lateral joint lines of the knee. Performance scores were based on both accuracy and time. A total physical examination performance score was derived for each joint. Scores for instructional groups were compared by a 2‐way analysis of variance with 1 repeated measure. Significant findings were further analyzed with post hoc tests. Results: All students performed significantly better on the knee examination, irrespective of instructional group ( F = 14.9; df = 1.25; P = .001). Moreover, the shoulder instruction group performed significantly better than the knee group on the overall assessment ( t = –3.0; df = 25; P < .01). Post hoc analyses revealed that differences in group performance were due to the shoulder group's higher scores on palpation of the biceps tendon ( t = –2.8; df = 25; P = .01), a soft tissue landmark. Both groups performed similarly on palpation of all other anatomic structures. Conclusions: The use of ultrasound appears to provide an educational advantage when learning musculoskeletal physical examination of soft tissue landmarks.